1978
DOI: 10.1093/nar/5.8.2809
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis of a self-complementary octanucleotide, dG-G-T-T-A-A-C-C by a modified triester method

Abstract: The synthesis of a self-complementary octanucleotide, d(G-G-T-T-A-A-C-C-), using a modified triester approach is described. The protected dinucleotides, d(Me2O)TribG(C1C6H4) ibG, d(Me2O)TrT(ClC6H4)T, d(Me2O)TrbzA(ClC6H4)bzA, and d(Me2O)TranC(ClC6H4)anC were synthesized by a one step triester procedure. After removal of the trityl group, the dinucleotides, dT(ClC6H4)T and danC (ClC6H4)anC were coupled to d(Me2O)TribG(ClC6H4)ibG and d(Me2O)TrbzA(ClC6H4)bzA, respectively to yield the respective tetranucleotides. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1979
1979
1988
1988

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Asterisks indicate the number of additional clones found that had the same recombinant segment. In JM105 (recA+) cells (clones [1][2][3][4][5][6][7][8][9][10][11][12], only the recombinant segment of clone 1 had an inverse orientation, and 94% of the endpoints occurred at Alu I sites. In JM109 (recA-) cells (clones [13][14][15][16][17], four of the five recombinant segments had the inverse orientation, and 20% of the endpoints occurred at Alu I sites.…”
Section: Discussionmentioning
confidence: 99%
“…Asterisks indicate the number of additional clones found that had the same recombinant segment. In JM105 (recA+) cells (clones [1][2][3][4][5][6][7][8][9][10][11][12], only the recombinant segment of clone 1 had an inverse orientation, and 94% of the endpoints occurred at Alu I sites. In JM109 (recA-) cells (clones [13][14][15][16][17], four of the five recombinant segments had the inverse orientation, and 20% of the endpoints occurred at Alu I sites.…”
Section: Discussionmentioning
confidence: 99%
“…RESULTS AND DISCUSSION Short, synthetic oligonucleotides can be synthesized relatively easily by either chemical (11,14,15,(21)(22)(23) or enzymatic methods (24). Such oligonucleotides have been used as primers for DNA (25) and RNA (26) sequence determinations, as hybridization probes to isolate cloned genes (27) and as detectors of specific mRNAs (28).…”
Section: Methodsmentioning
confidence: 99%
“…The key intermediates in this synthesis are the fully protected deoxyribonucleoside S'-p-chlorophenyl /3-cyanoethyl phosphotriesters, d-[(MeO)2Tr]NpCE, which are required in large quantities and high purity. These protected monomers were synthesized by using a modification of an approach originally described by Agarwal & Riftina (1978). This procedure involves phosphorylation of suitably protected 5'-0-(dimethoxytrityl)deoxyribonucleosides with a small excess of p-chlorophenyl bis(triazolide), followed by esterification with hydroacrylonitrile.…”
Section: Resultsmentioning
confidence: 99%